PENGARUH TEKNIK TIRU MODEL BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR - Maharani, Laura; Asri, Yasnur; Rasyid, Yulianti (Universitas Negeri Padang, 2018)
This article aims to describe the level of writing skills text procedures grade VII SMP Negeri 1 Pariaman. Type of this research is quantitative research with experimental methods. The results of the research there are three as follows. First, writing skills text procedures grade VII. 2 SMP Negeri 1 Pariaman before using the techniques resembled audiovisual media-assisted model is at a sufficient qualification (C) with an average value of 63.02. Second, the skills of writing text procedures grade VII. 2 SMP Negeri 1 Pariaman after using the techniques resembled audiovisual media-assisted models are on good qualifications (B) with an average value of 84.55. Third, based on the t-test, it was concluded that there is a significant influence in the use of techniques of audiovisual media-assisted models resembled towards writing skills text procedures grade VII SMP Negeri 1 thitung > ttabel because Pariaman (3.810 > 1.67).Â Kata Kunci: Pengaruh, Teknik Tiru Model, Media Audiovisual